Joint loads and muscle force distribution during classical and jazz - Blazkiewicz, M. (Acta of Bioengineering and Biomechanics, 2021)
Purpose: The objective of this study was to analyze the muscle force distribution and lower limb joint loading during two types of pirouettes and check which muscle in which pirouette generates the highest force and which joint is the most loaded. Methods: Skilled dancers (n = 16) performed single-turn pirouettes in jazz and classic styles. Kinematic and kinetic data were collected using the Vicon system and Kistler plates. The joint reaction forces and muscle forces were calculated using a musculoskeletal model in the AnyBody Modeling System. Results: No statistically significant differences were found for the duration of the turn in both pirouettes. The range of motion in all joints of supporting leg in sagittal plane and in hip joint in frontal plane for non-supporting leg were significantly higher in classic pirouette. The ankle joint is the most loaded joint in both pirouettes and its maximal value is significantly higher in classic pirouette. The force generated by ankle plantar flexors muscles is significantly greater in the jazz pirouette in turn phase. For the non-support limb, external hip rotators generate significantly greater force when performing the classic pirouette. Conclusions: It seems that early stage dancers may start their lessons with jazz pirouettes, where needed joint mobility is less. They also will increase muscle strength and body awareness, with such proceedings. A better awareness of the mechanical loads on the musculoskeletal system which a dancer performing pirouettes faces should have an impact on the way dance classes are conducted and choreographic elements are sequenced.